Molecular Epidemiology of Rabies Virus in the Territory of the Russian Federation - A. A. Deviatkin (Эпидемиология и вакцинопрофилактика, 2017)
In this study, we report the phylogenetic relationship of RABV circulating in Russia. A total of 81 new isolates obtained from different regions of Russia in 2008 - 2016 were partially sequenced. Evolutionary analysis based on 100 representative sequences of rabies virus N-gene fragments (1110 nt) with sample time span ranging from 1977 to 2016 was made by the Bayesian coalescent analysis. Temporal estimates for major evolutionary events were done. The division of steppe rabies virus group C to discrete subgroups was revealed. According to our data, this most widespread in the Russian Federation group emerged in the beginning of the 1940th. The presence of steppe rabies virus was detected in the Far East (Primorsky Krai). The most likely cause of this event is anthropogenic introduction.. For the first time, representatives of arctic rabies subgroup A2 were isolated in the north of European Russia and FranzJosef Land. Evolutionary analysis suggested relatively recent emergence of all rabies virus groups currently circulating in the territory of the Russian Federation.